Covid-19 : « La faim se nourrit de toutes les inégalités, de toutes les vulnérabilités ». Entretien avec Jean-François Riffaud, Directeur général d’Action contre la Faim, 28 janvier 2021 - Jean-François Riffaud (Tracés, 2021)
The interview with Jean-François Riffaud discusses the views of Action Against Hunger (ACF) on the nature and effects of the Covid-19 pandemic crisis, as well as on its own humanitarian practices. Even if the circulation and reproduction rate of the virus (also known as R0) was much lower than in France, public authorities in most poor countries took protection and lockdown measures with serious socio-economic and psychological effects. Between April and June 2020, for example, this resulted in a 20 to 50 percent drop in attendance at ACF-run care centres, especially those for children. Among other factors (such as conflicts), this has an effect on the increase in cases of malnutrition. Thus, the United Nations predicts that the number of people suffering from acute malnutrition will soon be two-hundred-and-thirty million worldwide (against one-hundred-and-fifty million by the end of 2020). In addition to the side-effects of protection measures, with a prevalence of malnutrition and food insecurity higher than the clinical prevalence linked to the virus, J.-F. Riffaud underlines a context of great uncertainty in which decision-making is particularly difficult. It is all the more difficult because the crisis highlights counterintuitive logics: for example, the populations most affected by the virus are not necessarily the most vulnerable in terms of malnutrition. This interview also reminds us of the extreme fragility of health and social protection systems in poor countries. It shows that hunger is the result of structural dysfunctions linked to specific and identifiable political and economic choices. The political nature of the issue also shows that we should not limit the representation of hunger to exceptional events (drought, wars, etc.). Nor should we reduce its management to a single technical act, at the risk of preventing us not only from understanding it but also from being able to look critically at the ambivalent and unexpected effects of certain actions, including those of non-governmental organisations. In the current period, despite the uncertainties and the risk of staff, especially expatriates, being carriers of the virus, ACF has decided to pursue its activities (emergency nutrition programmes, agro-ecological reinforcement, etc.). For the NGO, it is a question of remaining faithful to its “mandate towards the communities and its ethical path”. Finally, the crisis seems to validate three imperatives of a common agenda for all humanitarian NGOs: localisation of aid, partnership with civil society and local communities, and mutualisation, beyond the logic of simple profitability.